CENTRALIZATION OF FAMILY e-ARCHIVES THROUGH MEMORY PROCESS ANALOGY: Array - 1 (Arsip Nasional Republik Indonesia, 2021)
e-Archive or electronic archive is an archive that is stored and processed in a format where only a computer or electronic device can process it. In the making of e-Archives, researchers apply forms of memory processing which includes information (encoding), storage (storage), and information retrieval (retrieval stage). In this research, researchers used descriptive and literature study methods. Researchers found by using the combination of memory processing analogy and information processing theory, the centralization of e-Archive can help the community and government in the process of managing family’s important document. However, there are also some weaknesses that must be considered in it’s implementation.